The Improvement in Students’ Conceptual Understanding after Guided Inquiry Learning with Mind Mapping - Kusuma, Putri Ria; Sudarmin, Sudarmin; Putra, Ngurah Made Darma (Educational Management, 2021)
The implementation of learning in 4th grade SDN Gugus Ki Hajar Dewantara has inot guided the students ito find their iown concepts iof iknowledge iand ianswer analytical iquestions. The istudents feel ibored iand caused the lack iof istudents’ iconceptual iunderstanding iin ilearning imaterials. This research aimed to analyze the iimprovement in students’ conceptual iunderstanding iafter guided inquiry ilearning iwith imind imapping. The research method used quasi experimental iwith nonequivalent control group design. The iresearch implemented to 4th igrade istudents iof iSD Negeri Tlogowungu 01 iand SD Negeri Tlogowungu 03, Pati iRegency. iThe idata icollection techniques were idocumentation, observation, iand conceptual understanding itest in ithe iform of essay. The idata iwere ianalyzed iby igain iscore test iand T-test. ihe iresult irevealed ithat there iwas significant improvement in istudents’ conceptual understanding after iguided iinquiry ilearning iwith imind imapping. There iwas significant idifference in ithe iaverage iscores of conceptual understanding between the experimental class iand the icontrol iclass with isignification irate 5% iwith ithe iN-Gain iof iexperimental iclass iwas 0.85 which included in ihigh category while the control class was 0.51 which included in medium category. The result of independent test stated there was a difference between the experimental class and ithe icontrol iclass ishowed iby significance ivalue iof i0.003 i<0.05. iIt ishows ithat ithere iwas ian improvement in istudents’ iconceptual understanding after iguided inquiry learning with imind mapping. This iresearch ican be iused ias contribution of thoughts ito iimprove the ieducation quality in general and istudents’ achievements in specific.